Influence of Urban Settlements’ Geometry on Outdoor Thermal Conditions and Comfort: A Case Study of Kampung in Surabaya-Indonesia - Ronalmanto Ronalmanto; I Gusti Ngurah Antaryama; Sri Nastiti Nugrahani Ekasiwi (IPTEK Journal of Proceedings Series, 2020)
In urban areas, especially urban settlements, low thermal comfort at pedestrian height and the high use of building energy are two interrelated conditions. Geometry of built environment is a factor that correlates with thermal conditions of the location and comfort. Understanding how geometry of built environment affects conditions and thermal comfort can be the basis for improving thermal condition as well as increasing thermal comfort. This study examines the influence of urban settlement geometry to thermal conditions and thermal comfort of urban space. An experiment was carried out on ten blocks, consisting of two block models and two orientations: Blocks with Different Height-to-Width Ratio (H / W = 0.8-1.5-2.3) and Blocks with the Same Height-to-Width Ratio but With Different Left-Right Height (H / W = 1.5-1.5'-1.5 "), respectively in the North-South and East-West orientation. The ENVI-met 3.1 program was used to simulate the conditions and thermal comfort of the blocks in the hottest day conditions. The results of this study indicate the geometry of the urban settlement influences two factors or thermal environment, i.e., direct solar radiation reception or block irradiation duration and wind speed. Features of the geometry affecting the thermal conditions are angle of the sky opening and block's orientation towards incoming winds. These two features are regarded as the dominant factor influencing the overall thermal conditions and comfort of the settlement blocks. This study also confirms that hight-width (H/W) ratio as the main parameter governing thermal conditions and comfort of the block.